A Collection of all the Public Acts of Assembly, of the Province of North-Carolina 91 (1752) - (:unkn) unknown (My University, 1738)
"That iit shall not be lawfull to kill or deftroy any Deer, running wild in the Woods, or unfenced Ground, in this Government, by Gun, or any other Ways or Means whatfoever, between the Fifteenth Day of February, in each Year, and the Fifteenth Day of July fucceeding,"
Keywords: HUNTING REGULATION